Method for preparing etching-resistant Ni hard mask layer

By introducing H2 gas into magnetron sputtering method to regulate Ni film growth, the problem of poor etch resistance of existing mask materials to chlorine-based plasma etching is solved, and a dense and corrosion-resistant Ni film preparation is achieved, which is suitable for Resistant to chlorine-based plasma etching.

CN119465053AActive Publication Date: 2025-02-18NORTHWESTERN POLYTECHNICAL UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411668865.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing mask materials have poor etch resistance to chlorine-based plasma etching and cannot meet the needs of chlorine-based plasma etching.

Method used

The Ni film is deposited on the substrate surface by magnetron sputtering method. By introducing H2 gas as an etching gas in the vacuum chamber, the growth process of the Ni film is regulated, the growth of columnar crystals is suppressed, and the density and corrosion resistance of the Ni film are improved.

Benefits of technology

The Ni film prepared has a dense structure and a smooth surface, which significantly improves its corrosion resistance and etch resistance, and can be used as a mask material for chlorine-based plasma etching.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465053A_ABST
    Figure CN119465053A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing an etching-resistant Ni hard mask layer, and belongs to the technical field of micro-nano processing and thin films. The Ni film is prepared through a magnetron sputtering method, and the quality and performance of the Ni film are regulated and controlled by regulating and controlling key process parameters such as the Ar / H2 gas flow ratio, the sputtering air pressure, the substrate heating temperature and the sputtering power in the magnetron sputtering process. By the adoption of the method, the Ni film which is free of a columnar structure, smooth in surface, good in corrosion resistance, high in etching selection ratio and high in deposition rate is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of micro-nano processing and thin film technology, and in particular to a method for preparing an etching-resistant Ni hard mask layer. Background Art

[0002] Micro-nano processing technology is a key preparation technology in the fields of modern microelectronic chips, optoelectronic chips, biological and chemical microfluidic chips, micro-electromechanical systems, multifunctional micro-nano structure surfaces, etc. Among them, plasma etching is the core process of micro-nano processing technology, which is to transfer the mask pattern to the surface of the target substrate material, so as to finally realize the preparation of micro-nano devices and micro-nano patterns. Currently, the commonly used masks include: soft masks, such as photoresist masks, polymer masks such as PMMA; hard masks, commonly used metal materials such as Al, Cr, Ti, Ni, and inorganic non-metallic materials such as SiO2, Si3N4, Al2O3. However, these mask materials are mainly used as etching masks for conventional semiconductor materials such as Si, Ge and their compounds, and are used for fluorine-based gas plasma etching processes, which are relatively mature. With the continuous expansion of the application fields of micro-nano structure surfaces, there are more and more studies and applications on etching micro-nano structures on different substrate materials, such as etching of substrates such as spinel, II-VI compounds, and III-V compounds. However, fluorine-based gases are ineffective due to their low chemical activity and low volatility of the etching products of these materials, and a more active chlorine-based etching gas needs to be used. However, the above-mentioned soft masks, Al, Cr, Ti metal masks, and inorganic non-metallic mask materials such as SiO2, Si3N4, and Al2O3 have poor etching resistance to chlorine-based plasma and relatively small etching selectivity with the substrate material, and cannot meet the requirements of chlorine-based plasma etching resistance. Therefore, it is particularly important to develop new mask materials or mask preparation processes.

[0003] Relatively speaking, Ni metal film has good etching resistance and is firmly bonded to the substrate, and is a commonly used etching mask material. In addition, because Ni has excellent corrosion resistance, ductility and wear resistance, it is also widely used in the fields of corrosion protection and wear resistance. In the document "Study on the Organization and Corrosion Resistance of Nickel-Based Composite Films Prepared by Magnetron Sputtering" (Sun Kang, Master's Thesis of Shandong University of Science and Technology, 2019), Ni-Zr, Ni-Cr-Zr and other Ni-based alloy films were prepared by magnetron sputtering using Ar as the sputtering gas, which have good corrosion resistance; in the document "Experimental Study on Electrodeposition of Nickel Films with Variable Current Waveform" (Zhang Huajin, Master's Thesis of Henan University of Technology, 2023), the document "Research on the Corrosion Resistance of Metal Nickel Plating for Conductor Interconnection" (Wang Yuequan, Master's Thesis of Shanghai Jiaotong University, 2017) and the document "Research on Metal Nickel Electrodeposition Process and Coating Structure" (Li Fubin, Master's Thesis of Lanzhou University, 2015), Ni metal films were prepared by electrodeposition technology, and the results were studied. Its corrosion resistance; in the document "Application Basic Research on Laser-Assisted Preparation of Micro-Nano Structure Flexible Conductive Film" (Gao Liang, Master's Thesis of Lanzhou University, 2020), Ni metal grid film was prepared by electrodeposition technology, and its transparent conductive properties were studied; in the document "Research on Deposition of Metal Nickel Film on Glass by DC Magnetron Sputtering" (Han Li. Surface Technology, 2012, Vol. 41, No. 6, p. 66), high-purity Ar was used as the sputtering gas, and the Ni metal film was prepared by DC magnetron sputtering; the document "Preparation of Nickel Thin Film and Its Metal Silicide by Thermal ALD Technology" (Wu Liying, Qu Minni, Shen Zhiliang, Wang Ying, Cheng Xiulan. Micro-Nano Electronic Technology, 2019, Vol. 56, No. 6, p. 486) and the document "Plasma-Enhanced Atomic Layer Deposition of Ni”(Han-Bo-Ram Lee, Sung-Hwan Bang, Woo-Hee Kim, Gil Ho Gu, Young Kuk Lee, Taek-Mo Chung, Chang Gyoun Kim, Chan Gyung Park, and Hyungjun Kim. Japanese Journal of Applied Physics, 2010, 49(5): 05FA11-1-05FA11-4) used atomic layer deposition technology in the 250℃ reaction temperature window to prepare a high-purity, good conformality, continuous and smooth Ni metal film; the literature “Surface engineering for SiC etching with Ni electroplating masks”(Nour Beydoun, Mihai Lazar, Xavier Gassmann.International Semiconductor Conference (CAS), Oct. 2022, Poiana Brasov, Romania. pp. 119-122, 10.1109 / CAS56377.2022.9934701.hal-03856454) used electrodeposition technology to prepare a Ni mask for fluorine-based plasma etching of SiC substrates. The Ni film deposition rate is fast and the thickness is large; the literature "Fabrication of Nickel Plasma Etching Mask by Nano-Imprint Lithography and Electroless Plating" (Shingo Shimizu, Hideki Tanabe, Masaaki Yasuda, Yoshihiko Hirai. Journal of Photopolymer Science and In the paper “Study on Dry Etching of Silicon Carbide and Dielectric with Metal Mask” (Chen Gang, Wang Quanhui, Li Li, Liu Haiqi, Bai Song. The 17th National Conference on Compound Semiconductors, Microwave Devices and Optoelectronic Devices, Kaifeng, October 13-14, 2012), Ni mask was prepared by electron beam evaporation for fluorine-based plasma etching of SiC substrate and Si film, and a large etching selectivity was obtained. In the paper “Etching Selectivity and Surface Profile of GaN in the Ni, SiO2 and Photoresist Masks Using an Inductively Coupled Plasma” (Liann-Be CHANG, Su-Sir Liu and Ming-Jer JENG. Jpn. J. Appl. Phys., Part 1,2001,40(3A):1242-1243) used electron beam evaporation technology to prepare Ni film, which was used as a chlorine-based plasma etching mask for GaN thin film to obtain a large etching selectivity; the literature "Using Ni masks in inductively coupled plasma etching of high density hole patterns in GaN" (David SYHsu; Chul Soo Kim; Charles R.Eddy,Jr.; Ronald T.Holm; Richard L.Henry; JACasey; VA Shamamian; A. Rosenberg. J. Vac. Sci. Technol. B, 2005, 23: 1611–1614) used ion beam sputtering to prepare a Ni mask, which was used as a chlorine-based plasma etching mask for GaN thin films. The Ni film deposition rate was 7.4 nm / min, the structure was dense, and the surface was smooth and flat. .

[0004] In the preparation and application of the above-mentioned Ni film and Ni mask or film, the electrodeposition technology is the most widely used, with a fast deposition rate and a large Ni film thickness, but the deposited Ni film has a low adhesion strength, a loose structure, many pores, and a large surface roughness, so the corrosion resistance and etching resistance are poor; the atomic layer deposition Ni film has a dense structure, a smooth surface, and a very small roughness, but the deposition rate is very low, and a metal organic compound precursor is used, so the efficiency is low and the cost is high; the liquid phase deposition technology process is simple and efficient, but because it involves chemical reactions, the precious metal Pd needs to be used as a catalyst, and the liquid phase deposition process will have an adverse effect on the device preparation pre-sequence and subsequent processes; the electron beam evaporated Ni film, due to the inherent characteristics of the low energy of the evaporated atoms, makes the Ni film poor in density, low adhesion strength, and secondary sputtering occurs during the etching process; the ion beam sputtering deposited Ni film has a dense structure, a large adhesion strength, and a smooth surface, but the sputtering rate is slow, the film thickness is small, and a large-caliber ion source with high technical difficulty and cost is required. Relatively speaking, DC magnetron sputtering and RF magnetron sputtering have great advantages in the preparation of metal films such as Ni, and are widely used in the preparation of devices and masks. However, the prepared Ni film is prone to severe columnar crystal structure, and the columnar crystal structure becomes more serious with the increase of deposition rate and film thickness, resulting in rough surface and poor density of Ni film. Therefore, the prepared Ni film has insufficient etching resistance and corrosion resistance, which affects the accuracy of etching pattern and etching selectivity. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an etching-resistant Ni hard mask layer, so as to solve the above-mentioned technical problems.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing an etching-resistant Ni hard mask layer, comprising the following steps:

[0008] A Ni film is deposited on the substrate surface by magnetron sputtering;

[0009] The magnetron sputtering method comprises the following steps:

[0010] The pre-treated substrate is placed on the anode in the vacuum chamber of the magnetron sputtering coating machine, and 99.99% high-purity Ni is used as the target material, Ar gas is used as the sputtering gas, and H2 gas is used as the etching gas. Under vacuum conditions, the Ni target is sputtered to grow a Ni film;

[0011] The vacuum condition is a vacuum degree of <8×10 -4 Pa.

[0012] Furthermore, the substrate heating temperature is 100-250°C.

[0013] Furthermore, the sputtering gas pressure in the vacuum chamber is 0.15-0.5Pa.

[0014] Furthermore, the Ar gas flow rate is 25-40 sccm, and the H2 gas flow rate is 2.5-5.6 sccm.

[0015] Furthermore, the flow ratio of the Ar gas to the H2 gas is 7:1 to 10:1.

[0016] Furthermore, the sputtering power is 100-250W.

[0017] Beneficial effects of the present invention:

[0018] The present invention uses magnetron sputtering technology to prepare Ni thin film, and introduces an appropriate amount of H2 as etching gas into the vacuum chamber to regulate the growth process of the Ni film. H2 will be excited, decomposed and ionized in the plasma atmosphere in the vacuum chamber to obtain highly energetic and active H atoms and H + Ion, H / H + It has a strong corrosion and etching effect, and will etch away the Ni atoms with weaker bonding and lower diffusion ability deposited on the substrate, thereby inhibiting the growth of columnar crystals and helping to improve the compactness of the Ni film. The reduction of columnar structures can also reduce the surface roughness of the film. Since the Ni atoms at the junction of the columnar structure are highly active and easily chemically reacted, they are first corroded / etched during the corrosion or etching process, so the Ni film with a columnar structure has poor corrosion / etching resistance. The present invention effectively inhibits the growth of the columnar structure, and the prepared Ni film has a dense structure and a smooth surface, thereby improving the corrosion resistance and etching resistance of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a surface scanning electron microscope photograph of the deposited Ni film under the process parameters of sputtering power 100W, substrate temperature 100℃, gas pressure 0.5Pa, Ar gas flow rate 25sccm and H2 gas flow rate 2.5sccm (Ar:H2 gas flow rate ratio 10:1);

[0020] Figure 2Cross-sectional scanning electron microscope photograph of the deposited Ni film under the process parameters of sputtering power 100W, substrate temperature 100℃, gas pressure 0.5Pa, Ar gas flow rate 25sccm and H2 gas flow rate 2.5sccm (Ar:H2 gas flow rate ratio 10:1);

[0021] Figure 3 Surface atomic force microscopy images of the deposited Ni film under the process parameters of sputtering power 100W, substrate temperature 100℃, gas pressure 0.5Pa, Ar gas flow rate 25sccm and H2 gas flow rate 2.5sccm (Ar:H2 gas flow ratio 10:1);

[0022] Figure 4 It is a surface scanning electron microscope photograph of the deposited Ni film under the process parameters of sputtering power 190W, substrate temperature 150℃, gas pressure 0.3Pa, Ar gas flow rate 25sccm and H2 gas flow rate 2.5sccm (Ar:H2 gas flow rate ratio 10:1);

[0023] Figure 5 It is a cross-sectional scanning electron microscope photograph of a Ni film deposited under the process parameters of sputtering power 190W, substrate temperature 150℃, gas pressure 0.3Pa, Ar gas flow rate 25sccm and H2 gas flow rate 2.5sccm (Ar:H2 gas flow rate ratio 10:1);

[0024] Figure 6 It is an atomic force microscope photo of the surface of the deposited Ni film under the process parameters of sputtering power 190W, substrate temperature 150℃, gas pressure 0.3Pa, Ar gas flow rate 25sccm and H2 gas flow rate 2.5sccm (Ar:H2 gas flow rate ratio 10:1);

[0025] Figure 7 Surface scanning electron micrograph of the deposited Ni film under the process parameters of sputtering power 250W, substrate temperature 150℃, gas pressure 0.3Pa, Ar gas flow rate 35sccm and H2 gas flow rate 3.5sccm (Ar:H2 gas flow ratio 10:1);

[0026] Figure 8 It is a surface scanning electron microscope photograph of a Ni film deposited under process parameters of sputtering power 250W, substrate temperature 250°C, gas pressure 0.15Pa, Ar gas flow rate 40sccm and H2 gas flow rate 5.6sccm (Ar:H2 gas flow rate ratio ~7:1);

[0027] Fig. 9 This is a surface optical microscope photograph of the Ni film deposited after corrosion under the condition of adding H2 gas in Example 4 of the present invention;

[0028] Fig.10This is an optical microscope photo of the surface of the Ni film deposited after corrosion without adding H2 gas;

[0029] Fig.11 This is a scanning electron microscope photograph of a pattern etched after a Ni mask is prepared on a ZnS surface under the condition of adding H2 gas in Example 4 of the present invention;

[0030] Fig.12 This is a scanning electron microscope photograph of a pattern etched after a Ni mask is prepared on the surface of magnesium aluminum spinel (MgAl2O4) under H2 gas conditions in Example 3 of the present invention. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing an etching-resistant Ni hard mask layer, comprising the following steps:

[0032] A Ni film is deposited on the substrate surface by magnetron sputtering;

[0033] The magnetron sputtering method comprises the following steps:

[0034] The pre-treated substrate is placed on the anode in the vacuum chamber of the magnetron sputtering coating machine, and 99.99% high-purity Ni is used as the target material, Ar gas is used as the sputtering gas, and H2 gas is used as the etching gas. Under vacuum conditions, the Ni target is sputtered to grow a Ni film;

[0035] The vacuum condition is a vacuum degree of <8×10 -4 Pa, substrate temperature is 100℃~250℃.

[0036] In the present invention, the vacuum condition is preferably a vacuum degree of <6×10 -4 Pa, preferably <3×10 -4 Pa.

[0037] In the present invention, the substrate temperature is 100 to 250°C, preferably 120 to 240°C, more preferably 150 to 240°C, and even more preferably 200 to 220°C.

[0038] In the present invention, the sputtering gas pressure in the vacuum chamber is 0.1-0.5Pa, preferably 0.2-0.4Pa, and more preferably 0.3Pa.

[0039] In the present invention, the Ar gas flow rate is 25 to 40 sccm, preferably 30 to 35 sccm, and more preferably 30 sccm; the H2 gas flow rate is 2.5 to 5.6 sccm, preferably 3 to 5 sccm, and more preferably 3.5 to 4.5 sccm.

[0040] In the present invention, the flow ratio of the Ar gas to the H2 gas is 7:1 to 10:1, preferably 10:1.

[0041] In the present invention, the sputtering power is 100 to 250 W, preferably 120 to 250 W, more preferably 150 to 250 W, and even more preferably 190 to 250 W.

[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0043] Example 1

[0044] Step 1: Pre-treat the substrate

[0045] The polished Si substrate is first rinsed with deionized water to remove surface particles; then the substrate surface is wiped with cotton wool soaked in acetone and alcohol in turn to remove organic pollutants such as grease on the surface; then the substrate is ultrasonically cleaned with acetone and deionized water in turn; and then the substrate is blown dry.

[0046] Step 2: Prepare Ni film by magnetron sputtering

[0047] The specific preparation process is as follows:

[0048] Step 2.1: Place the pre-treated substrate on the anode in the vacuum chamber of the magnetron sputtering coating machine, place the 99.99% high-purity Ni target on the cathode, and pump the background vacuum of the coating machine to <8×10 -4 Pa, and heat the substrate to 100°C.

[0049] Step 2.2: Ar gas and H2 gas are introduced into the vacuum chamber, the Ar gas flow rate is set to 25 sccm, the H2 gas flow rate is set to 2.5 sccm, the Ar:H2 gas flow ratio is 10:1, and the pressure in the vacuum chamber is set to 0.5 Pa.

[0050] Step 2.3: Start the discharge for sputtering, set the sputtering power to 100 W, and the sputtering time to 60 minutes.

[0051] Step 2.4: After sputtering, wait for the substrate temperature to cool to room temperature and take out the sample.

[0052] Figure 1 is a surface scanning electron micrograph of the Ni film prepared in Example 1 of the present invention. Figure 1 It can be seen that the Ni film has a smooth, flat and clean surface, fine and uniform grains (grain size ~15nm) and a dense structure. Figure 2 is a scanning electron micrograph of a cross section of the Ni film prepared in Example 1 of the present invention. Figure 2It can be seen that the Ni film does not have an obvious columnar crystal structure, and the internal structure is dense without holes or gaps. Figure 3 is an atomic force micrograph of the surface of the Ni film prepared in Example 1 of the present invention. Figure 3 It can be seen that the surface roughness of the Ni film is only 0.8 nm. According to the test, the deposition rate of the Ni film is ~17 nm / min.

[0053] Example 2

[0054] Step 1: Pre-treat the substrate

[0055] The surface-polished ZnS substrate is first rinsed with deionized water to remove surface particles; then the substrate surface is wiped with absorbent cotton soaked in acetone and alcohol in turn to remove organic pollutants such as grease on the surface; then the substrate is ultrasonically cleaned with acetone and deionized water in turn; and then the substrate is blown dry.

[0056] Step 2: Prepare Ni film by magnetron sputtering

[0057] The specific preparation process is as follows:

[0058] Step 2.1: Place the pre-treated substrate on the anode in the vacuum chamber of the magnetron sputtering coating machine, place the 99.99% high-purity Ni target on the cathode, and pump the background vacuum of the coating machine to <8×10 -4 Pa, and heat the substrate to 150°C.

[0059] Step 2.2: Ar gas and H2 gas are introduced into the vacuum chamber, the Ar gas flow rate is set to 25 sccm, the H2 gas flow rate is set to 2.5 sccm, the Ar:H2 gas flow ratio is 10:1, and the pressure in the vacuum chamber is set to 0.3 Pa.

[0060] Step 2.3: Start the sputtering process by discharging and set the sputtering power to 190W and the sputtering time to 60 minutes.

[0061] Step 2.4: After sputtering, wait for the substrate temperature to cool to room temperature and take out the sample.

[0062] Figure 4 is a surface scanning electron micrograph of the Ni film prepared in Example 2 of the present invention. Figure 4 It can be seen that the Ni film has a smooth, flat and clean surface, fine and uniform grains (grain size ~20nm) and a dense structure. Figure 5 is a scanning electron micrograph of a cross section of the Ni film prepared in Example 2 of the present invention. Figure 5 It can be seen that the columnar crystal structure characteristics of the Ni film are very weak, and the internal structure is dense without holes or gaps. Figure 6FIG. 1 is an atomic force micrograph of the surface of the Ni film prepared in Example 2 of the present invention. Figure 6 It can be seen that the surface roughness of the Ni film is only 0.98 nm. According to the test, the deposition rate of the Ni film is 22 nm / min.

[0063] Example 3

[0064] Step 1: Pre-treat the substrate

[0065] The surface-polished MgAl2O4 substrate was first rinsed with deionized water to remove the particles on the surface; then the substrate surface was wiped with cotton wool soaked in acetone and alcohol in turn to remove organic pollutants such as grease on the surface; then the substrate was ultrasonically cleaned with acetone and deionized water in turn; and then the substrate was blown dry.

[0066] Step 2: Prepare Ni film by magnetron sputtering

[0067] The specific preparation process is as follows:

[0068] Step 2.1: Place the pre-treated substrate on the anode in the vacuum chamber of the magnetron sputtering coating machine, place the 99.99% high-purity Ni target on the cathode, and pump the background vacuum of the coating machine to <8×10 -4 Pa, and heat the substrate to 150°C.

[0069] Step 2.2: Ar gas and H2 gas are introduced into the vacuum chamber, the Ar gas flow rate is set to 35 sccm, the H2 gas flow rate is set to 3.5 sccm, the Ar:H2 gas flow ratio is 10:1, and the pressure in the vacuum chamber is set to 0.3 Pa.

[0070] Step 2.3: Start the discharge for sputtering, set the sputtering power to 250W, and the sputtering time to 60 minutes.

[0071] Step 2.4: After sputtering, wait for the substrate temperature to cool to room temperature and take out the sample.

[0072] Figure 7 : is a surface scanning electron micrograph of the Ni film prepared in Example 3 of the present invention. Figure 7 It can be seen that the surface of the Ni film is smooth, flat and clean, the grains are uniform (grain size ~50nm), and the structure is dense. According to the test, the surface roughness of the Ni film is ~2.5nm, and the deposition rate is ~32nm / min.

[0073] Example 4

[0074] Step 1: Pre-treat the substrate

[0075] The surface-polished ZnS substrate is first rinsed with deionized water to remove surface particles; then the substrate surface is wiped with absorbent cotton soaked in acetone and alcohol in turn to remove organic pollutants such as grease on the surface; then the substrate is ultrasonically cleaned with acetone and deionized water in turn; and then the substrate is blown dry.

[0076] Step 2: Prepare Ni film by magnetron sputtering

[0077] The specific preparation process is as follows:

[0078] Step 2.1: Place the pre-treated substrate on the anode in the vacuum chamber of the magnetron sputtering coating machine, place the 99.99% high-purity Ni target on the cathode, and pump the background vacuum of the coating machine to <8×10 -4 Pa, and heat the substrate to 250°C.

[0079] Step 2.2: Ar gas and H2 gas are introduced into the vacuum chamber, the Ar gas flow rate is set to 40 sccm, the H2 gas flow rate is set to 5.6 sccm, the Ar:H2 gas flow ratio is ~7:1, and the pressure in the vacuum chamber is set to 0.15 Pa.

[0080] Step 2.3: Start the discharge for sputtering, set the sputtering power to 250W, and the sputtering time to 60 minutes.

[0081] Step 2.4: After sputtering, wait for the substrate temperature to cool to room temperature and take out the sample.

[0082] Figure 8 is a surface scanning electron micrograph of the Ni film prepared in Example 4 of the present invention. Figure 8 It can be seen that the surface of the Ni film is smooth, flat and clean, contains grains of different sizes (average grain size ~65nm), and has a dense structure. According to the test, the surface roughness of the Ni film is ~2.94nm, and the deposition rate is ~40nm / min.

[0083] Fig. 9 The corrosion test results of the Ni film prepared in Example 4 of the present invention are shown in Figure 1, wherein the corrosion conditions are: immersion in a 3.5% NaCl solution at 45°C for 48 hours. For comparison, a Ni film was prepared using the same deposition process parameters without adding H2 gas, and a corrosion test was performed on it under the same conditions. The results are shown in Figure 1. Fig.10 As shown. Fig. 9 and Fig.10It can be seen that H2 gas is added in the method of the present invention, and only discrete corrosion pits are produced on the surface of the prepared Ni film. The corrosion pits have a low density and a small area, so the degree of corrosion is very small. However, the Ni film prepared without adding H2 gas has corrosion cracks in addition to the corrosion pits, and the density of the cracks and pits is very large, and the cracks are very long, so the corrosion is serious.

[0084] Fig.11 The Ni film prepared in Example 4 of the present invention is an etching mask, and the microstructure etched on the ZnS substrate has a Ni film thickness of 280 nm (deposition time of 7 min), an etching depth of 5 μm, and an etching selectivity of 17.86:1. The ICP etching parts are: excitation power 400 W, bias power 240 W, BCl3 gas flow 40 sccm, Ar gas flow 20 sccm, gas pressure 1 Pa, and time 70 min. It can be seen that the Ni film prepared by the method of the present invention has good resistance to chlorine-based plasma etching. After etching, the Ni mask remains intact, and the etching selectivity is large, which can be well used as an etching mask material for II-VI compound semiconductors.

[0085] Fig.12 The Ni film prepared in Example 3 of the present invention is an etching mask, and the microstructure etched on the magnesium aluminum spinel (MgAl2O4) substrate has a Ni film thickness of 480nm (deposition time is 15min), an etching depth of 2.4μm, and an etching selectivity of 5.09:1. The ICP etching parts are: excitation power 400W, bias power 240W, BCl3 gas flow 40sccm, Ar gas flow 20sccm, gas pressure 1Pa, and time 70min. It can be seen that the Ni film prepared by the method of the present invention has good resistance to chlorine-based plasma etching. After etching, the Ni mask remains intact, and the etching selectivity is relatively large, which can be well used as an etching mask material for MgAl2O4.

[0086] It can be seen from the above embodiments that the present invention provides a method for preparing an etching-resistant Ni hard mask layer. It can be seen from the above experimental verification that by using the method of the present invention, we obtain a Ni film with no columnar structure, compactness, smooth surface, good corrosion resistance, high etching selectivity, and fast deposition rate.

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an etching-resistant Ni hard mask layer, characterized in that: The following steps are involved: A Ni film is deposited on the substrate surface by magnetron sputtering; The magnetron sputtering method comprises the following steps: The pre-treated substrate is placed on the anode in the vacuum chamber of the magnetron sputtering coating machine, and 99.99% high-purity Ni is used as the target material, Ar gas is used as the sputtering gas, and H2 gas is used as the etching gas. Under vacuum conditions, the Ni target is sputtered to grow a Ni film; The vacuum condition is a vacuum degree of less than 8×10 -4 Pa.

2. The method for preparing an etching-resistant Ni hard mask layer according to claim 1, characterized in that: The substrate heating temperature is 100°C to 250°C.

3. The method for preparing an etching-resistant Ni hard mask layer according to claim 1, characterized in that: The sputtering gas pressure in the vacuum chamber is 0.15-0.5 Pa.

4. The method for preparing an etching-resistant Ni hard mask layer according to any one of claims 1 to 3, characterized in that: The Ar gas flow rate is 25-40 sccm, and the H2 gas flow rate is 2.5-5.6 sccm.

5. The method for preparing an etching-resistant Ni hard mask layer according to claim 4, characterized in that: The flow ratio of the Ar gas to the H2 gas is 7:1 to 10:

1.

6. The method for preparing an etching-resistant Ni hard mask layer according to claim 1, characterized in that: The sputtering power is 100-250W.

Citation Information

Patent Citations

  • Nano-crystalline Mg-Ni multilayer composite film and preparation method thereof

    CN101831619A

  • Method for preparing ceramic thin film circuit by taking electroplated nickel layer as mask layer

    CN110993556A

  • Preparation method of low-cost inclined-angle-controllable inclined-table-board nickel oxide / gallium oxide heterojunction power diode

    CN114744028A

  • Method for preparing amorphous alloy protective film on polyimide surface by magnetron co-sputtering process

    CN117026191A

  • Method for nickel plating treatment on surface of steel belt of power battery shell

    CN117587374A